Born wicked - Spotswood, Jessica (New York : Speak, 2013)
In an alternate New England of 1900, where the Brotherhood dominates and controls society, sixteen-year-old Cate Cahill has struggled since her mother's death to keep secret that she and her younger sisters are witches, but when a governess arrives from the Sisterhood, everything changes.
Booklist
Horn Book
School Library Journal
Booklist, January 2012
Bulletin (Center for Children's books), March 2012
Horn Book, November 2012
Keywords: Families -- New England -- Juvenile fiction; Governesses -- Juvenile fiction; Sisters -- Juvenile fiction; Witches -- Juvenile fiction; Family life -- Fiction; Governesses -- Fiction; Sisters -- Fiction; Witches -- Fiction; Family life -- New England -- Fiction; Governesses -- Fiction; Sisters -- Fiction; Witches -- Fiction; New England -- History -- 20th century -- Juvenile fiction; New England -- Fiction; New England -- History -- Fiction